“Why Can’t I Play?”: Transdisciplinary Learnings for Children with Disability’s Sport Participation - Darcy, Simon (2020)
This article explores the constraints to mainstream sports participation of children with disability in community sports clubs and schools through their lived experiences and the perceptions of parents, teachers, coaches, and club officials. It does so by administering an open-ended survey instrument to a sample of participants recruited from schools, sporting facilities, and disability organizations in New South Wales and Victoria, Australia. The data were analysed through a transdisciplinary conceptual framework which brought together the social model of disability (disability studies) with the leisure constraints framework (leisure studies), which have been encouraged by both academics and practitioners. The findings identified ableist and disablist practices, creating an enabled understanding of the facilitators for social inclusion. Participants perceived that interrelated intrapersonal, interpersonal, and structural constraints excluded children from their desired sporting activities. Through applying the social model of disability to the leisure constraints framework, the findings and discussion showed that a great deal of what had been considered intrapersonal constraints of the child with disability could be reinterpreted as interpersonal and structural constraints through enabling socially inclusive practices. The implications are that a social model of disability brings a new social lens to understanding constraints to sport participation for children with disability and can produce effective strategies for inclusion in sport at schools and community sport clubs.